2002
DOI: 10.1007/s00299-002-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

RAPD, ISSR and RFLP fingerprints as useful markers to evaluate genetic integrity of micropropagated plants of three diploid and triploid elite tea clones representing Camellia sinensis (China type) and C. assamica ssp. assamica (Assam-India type)

Abstract: An efficient in vitro propagation method using enhanced axillary branching cultures produced plants from nodal explants of three mature, elite tea clones: diploid UPASI 26 and UPASI 27 (2n=2x=30) representing Camellia sinensis (China type) and triploid UPASI 3 (2n=3x=45) representing C. assamica ssp. assamica (Assam-India type). The genetic fidelity of the micropropagated plants of these three tea clones was assessed by analysing their nuclear, mitochondrial (mt), and chloroplast (cp) genomes using multiple mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…Although radiation is very effective in inducing mutation, many other factors, such as the auxin-to-cytokinin ratio and their perspective concentration, nutritional conditions and in vitro stress, may also induce somaclonal variation (Devarumath et al 2002). This may account for why four adventitious buds with mutant phenotypes were also observed in the control group, equivalent to a mutant frequency of 0.47% (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Although radiation is very effective in inducing mutation, many other factors, such as the auxin-to-cytokinin ratio and their perspective concentration, nutritional conditions and in vitro stress, may also induce somaclonal variation (Devarumath et al 2002). This may account for why four adventitious buds with mutant phenotypes were also observed in the control group, equivalent to a mutant frequency of 0.47% (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…In turn, high probability of genetic change occurs in callus and protoplast culture (Krishna et al 2016). However, irrespective of the source of plant material, somaclonal variation cannot be excluded, as it was demonstrated in study on Camellia sinensis and C. assamica, in which organized meristem cultures were not always genetically true-to-type (Devarumath et al 2002). Also Evans (1988) reported considerable variation in adventitious Nicotiana alata plants regenerated directly from leaf explants without a callus intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Devarumath et al (2002) did not detect any polymorphism in plastid genome of the micropropagated plants of three tea clones. The chloroplast genome has been found to remain stable also in regenerants of Coffea arabica (Rani et al 2000) and F. vulgare (Bennici et al 2004).…”
Section: Discussionmentioning
confidence: 71%
“…Kuznetsova et al (2005), performing ISSR analysis on Pisum sativum regenerants, found that the percentage of polymorphism ranged from 0.7% to 15%. In Camellia somaclones, ISSR markers allowed the detection of 12% polymorphism (Devarumath et al 2002). Interestingly in S. tuberosum Sharma et al (2007) found a very low level of AFLP marker profile variation amongst plants regenerated (Bennici et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation